2011
DOI: 10.1002/ardp.201100065
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Antitumor‐Active Arglabin Derivatives

Abstract: Arglabin derivatives varied at the endo- or exo-cyclic double bond were synthesized and studied in a colorimetric sulforhodamine B assay for their cytotoxicity. Variations on the endocyclic double bond led to compounds of reduced cytotoxicity whereas derivatives from the reaction of the α-methylene-γ-butyrolactone moiety led to compounds of similar or only slightly reduced cytotoxicity but different, cell line-dependent selectivity. In addition, arglabin is an excellent starting material for the synthesis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
(29 reference statements)
0
21
0
Order By: Relevance
“…86 In a recent study involving arglabin ( 203 ), amine ( 205-206, 210-212 ), thiol derivatives ( 208-209 ), and other derivatives involving small structural changes ( 204 , 207 ) to the exocyclic methylene-γ-lactone and periphery of the molecule were prepared; their biological activities were analyzed (Figure 23). 79c The Michael adducts were all active at low micromolar IC 50 values (2-20 μM) for cytotoxicity to cervical, lung, melanoma, ovarian, colon, thyroid, and breast cancer cell lines, similar to the parent compound, where as the structural changes ( 204 , 207 , data not shown) abolished activity altogether (Table 5). …”
Section: αβ-Unsaturated Esters and Lactonesmentioning
confidence: 87%
See 1 more Smart Citation
“…86 In a recent study involving arglabin ( 203 ), amine ( 205-206, 210-212 ), thiol derivatives ( 208-209 ), and other derivatives involving small structural changes ( 204 , 207 ) to the exocyclic methylene-γ-lactone and periphery of the molecule were prepared; their biological activities were analyzed (Figure 23). 79c The Michael adducts were all active at low micromolar IC 50 values (2-20 μM) for cytotoxicity to cervical, lung, melanoma, ovarian, colon, thyroid, and breast cancer cell lines, similar to the parent compound, where as the structural changes ( 204 , 207 , data not shown) abolished activity altogether (Table 5). …”
Section: αβ-Unsaturated Esters and Lactonesmentioning
confidence: 87%
“…Reduction of the exocyclic methylene routinely eliminates biological activity, with some exceptions, even at high micromolar concentrations. 79 Several reviews have covered the biological importance and therapeutic potential of α-methylene-γ-lactone-containing compounds. 80 Therefore, the thiol reactivity of these Michael acceptors with cysteines and GSH will be the focus here.…”
Section: αβ-Unsaturated Esters and Lactonesmentioning
confidence: 99%
“…Arborescin (30) was generated from arglabin (2) by hydrogenation. [18] Bhat et al also www.eurjoc.org obtained amino analogues of ludartin (31), a potent and selective cytotoxic agent, [19] by use of a Michael addition at the exocyclic double bond of the α-methylene γ-lactone as a key step (Scheme 3). Less common guaianolides have been used in the synthesis of several derivatives with fascinating structural diversity.…”
Section: Guaianolide Strategiesmentioning
confidence: 99%
“…Many STLs exhibit important pharmaceutical properties. For example, thapsigargin from Thapsia laciniata has been used in clinical trials to treat advanced solid tumors (Drew et al, 2013), and arglabin from Artemisia glabella has been shown to selectively inhibit the growth of lung, liver and ovarian cancer cells but to exert fewer side effects on normal cells (Csuk et al, 2012). Xanthanolides are bicyclic STLs in which a five carbon-membered γ-lactone ring is fused to a seven carbon-membered carbocycle (Supplementary Figure 1).…”
Section: Introductionmentioning
confidence: 99%